INNOVATIVE METHODS OF TEACHING ENGLISH IN UZBEKISTAN: INNOVATIVE METHODS OF TEACHING ENGLISH IN UZBEKISTAN - Khamidullaeva, Tursinay (Журнал иностранных языков и лингвистики, 2025)
In Uzbekistan, the importance of English has been increasingly recognized as a global language of communication, business, and academia. As a result, the country’s educational system has undergone significant reforms to enhance English language learning at all levels. While traditional methods have long been dominant, recent innovations in teaching methods reflect the need for more dynamic and interactive approaches to ensure that students not only learn English but also become proficient in using it in real-life situations. This article explores the innovative methods being employed in Uzbekistan's school education to teach English, emphasizing their impact on student learning, teacher development, and future educational goals.